2014
DOI: 10.1186/1297-9686-46-35
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphism and haplotype effects associated with somatic cell score in German Holstein cattle

Abstract: BackgroundTo better understand the genetic determination of udder health, we performed a genome-wide association study (GWAS) on a population of 2354 German Holstein bulls for which daughter yield deviations (DYD) for somatic cell score (SCS) were available. For this study, we used genetic information of 44 576 informative single nucleotide polymorphisms (SNPs) and 11 725 inferred haplotype blocks.ResultsWhen accounting for the sub-structure of the analyzed population, 16 SNPs and 10 haplotypes in six genomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 55 publications
3
35
0
Order By: Relevance
“…This study revealed six genomic regions affecting DYDs for SCS (Abdel‐Shafy et al . ). The identified loci have been further validated in different datasets of subsequent generations using SCS (Abdel‐Shafy et al .…”
Section: Association Of Snps With Clinical Mastitis Compared To Previmentioning
confidence: 97%
See 4 more Smart Citations
“…This study revealed six genomic regions affecting DYDs for SCS (Abdel‐Shafy et al . ). The identified loci have been further validated in different datasets of subsequent generations using SCS (Abdel‐Shafy et al .…”
Section: Association Of Snps With Clinical Mastitis Compared To Previmentioning
confidence: 97%
“…) for 10 single nucleotide polymorphisms (SNPs) that had previously been significantly associated with DYDs for SCS (Abdel‐Shafy et al . ). Primers of genotyped SNPs are described in Table .…”
Section: Association Of Snps With Clinical Mastitis Compared To Previmentioning
confidence: 97%
See 3 more Smart Citations